2021
DOI: 10.3390/pathogens10111507
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lactic Acid on Wound Healing, Cell Growth, Cell Cycle Kinetics, and Gene Expression of Cultured Junctional Epithelium Cells in the Pathophysiology of Periodontal Disease

Abstract: Lactic acid (LA) is short-chain fatty acid, such as butyric acid and propionic acid, that is produced as a metabolite of lactic acid bacteria, including periodontopathic bacteria. These short-chain fatty acids have positive effects on human health but can also have negative effects, such as the promotion of periodontal disease (PD), which is caused by periodontal pathogens present in the gingival sulcus. PD is characterized by apical migration of junctional epithelium, deepening of pockets, and alveolar bone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Several studies also reported its ability to prevent atherosclerotic lesions [ 37 ], skin problems [ 38 ], and cancer [ 39 ]. Lactic acid (LA), identified as another major compound present in the extract, is essentially a short-chain fatty acid, such as butyric acid and propionic acid, produced as a metabolite of lactic acid bacteria, including periodontopathic bacteria [ 40 ]. These short-chain fatty acids have been cited to have positive effects on human health.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies also reported its ability to prevent atherosclerotic lesions [ 37 ], skin problems [ 38 ], and cancer [ 39 ]. Lactic acid (LA), identified as another major compound present in the extract, is essentially a short-chain fatty acid, such as butyric acid and propionic acid, produced as a metabolite of lactic acid bacteria, including periodontopathic bacteria [ 40 ]. These short-chain fatty acids have been cited to have positive effects on human health.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that lactate inhibited the expression of alkaline phosphatase (ALP) through G protein‐coupled receptor 81 α subunit signal and reduced autophagy through the MCT1‐mTOR signal pathway, thus inhibiting the osteogenic differentiation of human periodontal ligament stem cells 11 . Importantly, it has been demonstrated that lactate in high concentration increased the mRNA expression of inflammatory factors such as integrin α5, IL‐6, IL‐8, intercellular adhesion molecule‐1, and receptor activator of nuclear factor κB ligand and stimulated junctional epithelial cells, thus aggravating PD 9 …”
Section: Discussionmentioning
confidence: 99%
“…The lactate in PD originates from bacteria and tissue metabolism in the subgingival plaque, 9 resulting in higher lactate levels in the gingival crevicular fluid of patients with PD than in healthy individuals. 10 In this study, we observed substantially higher lactate content in the clinical periodontal tissues when compared to the levels in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation